Early detection of mental health problems in university students: Detección temprana de problemas de salud mental en universitarios - Espinoza García, Allyson Dajana (2024)
Due to community transmission and the increase in cases during the COVID-19 pandemic, preventive measures had to be adopted, including social isolation and quarantine, which have had effects on people's mental health. Thus, the restriction of free movement, the discontinuity of routines, the decrease in social interaction, the lack of traditional learning methods, as well as the new academic, technological and psychological demands have generated an increase in tension, stress and anxiety in young people.